1997
DOI: 10.1002/(sici)1099-0739(199708)11:8<635::aid-aoc625>3.3.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Superoxide Dismutase Isozymes by Methylmercury

Abstract: A study of alterations in two mammalian superoxide dismutases (SODs), Cu,Zn-SOD and Mn-SOD, caused by methylmercury has been reviewed. Mechanisms for the isozymeselective decrease in MnSOD activity by the organometallic compound observed in vivo have been extensively examined by experiments with purified enzyme preparations. ©

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…It is recognized that unlike methylmercury ions, mercury ions are bifunctional and bind not only to sulfhydryl groups but also to amino groups (Webb 1966). Thus, a change in native form of Mn-SOD involving decreased enzyme activity could be initiated after covalent attachment of mercury ions to the protein through reactive amino acid residues including Cys196 (Kumagai et al 1997). In our preliminary study, it was found that mercury ions were covalently bound to the Mn-SOD precipitated during reaction with an excess amount of HgCl 2 and the ratio of moles of mercury bound to moles of Mn-SOD was more than 10 (Y. Noto et al, unpublished observation).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…It is recognized that unlike methylmercury ions, mercury ions are bifunctional and bind not only to sulfhydryl groups but also to amino groups (Webb 1966). Thus, a change in native form of Mn-SOD involving decreased enzyme activity could be initiated after covalent attachment of mercury ions to the protein through reactive amino acid residues including Cys196 (Kumagai et al 1997). In our preliminary study, it was found that mercury ions were covalently bound to the Mn-SOD precipitated during reaction with an excess amount of HgCl 2 and the ratio of moles of mercury bound to moles of Mn-SOD was more than 10 (Y. Noto et al, unpublished observation).…”
Section: Resultssupporting
confidence: 79%
“…In our preliminary study, it was found that mercury ions were covalently bound to the Mn-SOD precipitated during reaction with an excess amount of HgCl 2 and the ratio of moles of mercury bound to moles of Mn-SOD was more than 10 (Y. Noto et al, unpublished observation). We have previously reported that loss of activity of murine Mn-SOD caused by methylmercuric chloride is due to conformational change through covalent attachment to methylmercury ions without sedimentation (Shinyashiki et al 1996;Kumagai et al 1997). Therefore, the present study indicates that mercury ions and methylmercury ions inhibit murine Mn-SOD activity via different mechanisms.…”
Section: Resultsmentioning
confidence: 95%
“…They found that the sensitivity of HeLa cells to MeHg was decreased by the overexpression of Mn-SOD, suggesting that the formation of superoxide anions in the mitochondria might be involved in the mechanism(s) involved in the cytotoxicity of MeHg. We have attempted to examine the mechanism involved in the relationship between Mn-SOD and MeHg (Kumagai et al, 1997;Shinyashiki et al, 1996). Levels of mRNA and protein synthesis for Mn-SOD were unaffected by MeHg administration.…”
Section: Oxidative Stress and S-mercurationmentioning
confidence: 99%
“…Although levels of mRNA and protein synthesis of Mn-SOD were unaffected by MeHg administration, MeHg caused a facile reduction in the activity, and a drastic decrease in the native form, of Mn-SOD (but not of Cu,Zn-SOD) with purified enzyme preparations. It was subsequently shown that the S -mercuration of Mn-SOD, through Cys196, by MeHg results in a decrease in the enzyme activity in vivo [14]. Therefore, the selective inhibition of Mn-SOD activity caused by S -mercuration could play a critical role in MeHg-induced neurotoxicity because SOD protects the cell against oxidative stress by scavenging superoxide.…”
Section: S-mercuration Of Proteins By Mehgmentioning
confidence: 99%